2019
DOI: 10.1038/s41523-019-0117-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and epidemiological significance of breast cancer subtype reclassification based on p53 immunohistochemical expression

Abstract: TP53 mutations are common in breast cancer and are typically associated with more aggressive tumor characteristics, but little is known about the clinicopathological and epidemiological relevance of p53 protein expression, a TP53 mutation surrogate, in breast cancer subtypes. In this study of 7226 Chinese women with invasive breast cancer, we defined breast cancer subtypes using immunohistochemical (IHC) measures of hormone receptors and HER2 in conjunction with histologic gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 59 publications
4
29
1
Order By: Relevance
“…In our study detected TP53 protein expression by immunohistochemistry reflected the mutant TP53 gene and we found that negative TP53 expression was a favorable prognostic indicator for better overall survival, however, it was not an independent prognostic factor in the multivariate analysis. Similar results have been previously reported [29,3,28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study detected TP53 protein expression by immunohistochemistry reflected the mutant TP53 gene and we found that negative TP53 expression was a favorable prognostic indicator for better overall survival, however, it was not an independent prognostic factor in the multivariate analysis. Similar results have been previously reported [29,3,28].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other studies that outlined the role of TP53 in the progression of breast carcinoma and indicated a poor prognosis [3,28]. The high frequency of TP53 expression in the TNBC is an independent prognostic factor, which might aid in identifying subgroups of TNBC patients who are more likely to have a poor outcome and to whom specific therapies might be directed [29,3]. In our study detected TP53 protein expression by immunohistochemistry reflected the mutant TP53 gene and we found that negative TP53 expression was a favorable prognostic indicator for better overall survival, however, it was not an independent prognostic factor in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 90%
“…The UICC TNM System was adopted to classify the clinical stage of the disease at presentation [21]. Evaluation of the Estrogen receptor (ER), Progesterone receptor (PR) and HER2 contents of the primary tumours was performed through IHC staining of the formalin-fixed paraffin-embedded tissue blocks using Dako kits (Denmark) including the specific monoclonal antibodies [14], [15]. Other recorded subtypes included: -ER (positive)/PR (negative)/HER2 (positive); -ER (negative)/PR (positive)/HER2 (positive); -ER (positive)/PR (negative)/HER2 (negative); and -ER (negative)/PR (positive)/HER2 (negative).…”
Section: Methodsmentioning
confidence: 99%
“…They usually respond well to hormonal treatment but poorly to conventional chemotherapy. While Luminal A could be adequately controlled with endocrine treatment, luminal B (triple positive TP) phenotypes often tend to be more proliferative, yielding relatively higher grade and recurrent tumours; thus, recommending combined chemotherapy and hormonal treatment [10], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry assessments were made for the expression of ER, PR and HER2 as described previously [25,26]. Breast cancers were classified into luminal A, luminal B, HER2 overexpression and triple negative (TN).…”
Section: Molecular Subtyping By Immunohistochemistrymentioning
confidence: 99%